Développer le désert : anciennes et nouvelles utopies - Jean-Robert Henry; Jean-Louis Marçot; Jean-Yves Moisseron (L’Année du Maghreb)
Desert and Development: Two seemingly contradictory terms, though often closely associated in practices and imaginations. In both the religious traditions of the Mediterranean and under the successive labels of "progress", "development" and "globalization", the idea of civilization has repeatedly found its opposite, its enhancer and its complement when referring to the desert: when civilization fails to conquer the desert, it reverts to desert. The interaction of representations around the contemporary variants of the Culture / Nature relation has ceaselessly fueled for two centuries an extensive literature on the desert, in which the relation between desert and developed space is not only a confrontation between two spaces, but also between two mythical eras of the world, two visions of human destiny.This vision is also projected into practical utopias – old and new – of desert enhancement. This study will focus on two of them – significantly different in time, spirit and effects: the desert irrigation projects and the plans for solar energy exploitation. The former aimed at mobilizing water resources in the desert to “make it grow green again” and expand cultivated areas; they sparked great interest among scientists and politicians in the late 19th century but were only finalized, like the trans-Saharan railway, in novels. It was not until independence that post-colonial States took over part of the projects.The solar energy project is less about developing the desert than it is about using the sun’s sterilizing energy for sustainable development throughout the Euro-Mediterranean region. The Mediterranean Solar Plan, a flagship project of the Union for the Mediterranean, is backed by large financial and technology companies who invest in renewable energy and dream of the Sahara as the future powerhouse of Europe. But by associating the desert too closely to European development, little space is left to the expectations of Saharan societies for the development of their living space and the project is likely to encounter considerable technical and political setbacks.